A comparison of steam and oxygen fed biomass gasification through a techno-economic-environmental study. (15th March 2020) - AlNouss, Ahmed; McKay, Gordon; Al-Ansari, Tareq
Highlights: The study evaluates generation of sustainable products from biomass gasification. Two types of gasifying medium; oxygen and steam, are compared. The article considers recycling of a blended feed of multiple biomass sources. Aspen plus is utilised to simulate and integrate the different processes. Poly-generation of Fisher-Tropsch liquids, methanol, urea and power is considered. Abstract: Economically, fossil fuels remain the main source of energy despite their high emissions of greenhouse gases. However, biomass, a renewable fuel with CO2 neutrality, has experienced widespread attention as a potential contributor to sustainable development of the energy sector. Gasification is an important thermochemical process that converts biomass feedstock into H2 -rich combustible gases, which are favoured by wide downstream applications. The use of pure steam or oxygen as a gasifying agent is preferred to increase the yield of combustible gases. Consequently, hydrogen is utilised as an important intermediary in the generation of value-added products such as urea, fuels and power. This study compares the biomass gasification using oxygen-only and steam-only gasifying agents. Moreover, the study examines a poly-generation system that consumes biomass feedstock of multiple sources to produce high grade Fisher-Tropsch liquids, methanol, urea, and power. To achieve this aim, four Aspen Plus simulation flowsheets are developed considering both gasifiying agents and compared utilising the built-in economic and environmental capabilities. The results obtained from the economic and environmental evaluation demonstrate the excellence of steam-only biomass gasification in providing profitable and cleaner products. The methanol production using steam gasification is the most economical solution with a net profit per input of $0.12 per kg of biomass input and the lowest emissions pathway with 0.68 kg of CO2 -e per biomass input. The relative nature of the results can offer diverse perspectives depending on the market situation of the products. Consequently, analysing the results relative to production capacity, power generation using steam gasification achieves a net profit approximated at $0.80 per kg of product, whilst methanol production using steam gasification remains the lowest environmental impact solution with 2.32 kg of CO2 -e per output product.